Einfluss frühkindlicher Stresserfahrungen und traumatisierender Lebensereignisse auf das Schmerzempfinden - Tesarz, Jonas; Gerhardt, Andreas; Eich, Wolfgang (Der Schmerz, 2018)
Adult pain perception is influenced substantially by interactions between mind, body, and social environment during early life. Early stress exposure and traumatic life events induce powerful psychophysical stress reactions that exert multiple neurofunctional processes. This has significant implications for pain perception and pain processing. As part of this review, the complex relationships between traumatic stress experiences and associated psychobiological mechanisms of chronic pain will be discussed. Based on selected studies, psychophysiological findings are presented and possible underlying mechanisms are discussed. The article concludes with a discussion of potential implications for treatment.
Gesehen am 14.05.2019